Human glyceraldehyde-3-phosphate dehydrogenase: mRNA levels and enzyme activity in developing muscle. - Edwards, Y H (1985)
Analysis of human glyceraldehyde-3-phosphate dehydrogenase mRNA revealed that levels in adult skeletal muscle are 12-fold greater per microgram of polyadenylated RNA than in fetal skeletal muscle, whereas in cardiac muscle RNA levels were about equal in fetal and adult tissue. The mRNA levels correlate well with glyceraldehyde 3-phosphate dehydrogenase enzyme activities. There was no evidence for fetus- or tissue-specific forms.